2018
DOI: 10.1096/fj.201800485rr
|View full text |Cite
|
Sign up to set email alerts
|

T‐lymphocyte–specific knockout of IKK‐2 or NEMO induces T h 17 cells in an experimental nephrotoxic nephritis mouse model

Abstract: Experimental nephrotoxic serum nephritis (NTN) is a model for T‐cell–mediated human rapid progressive glomerulonephritis. T‐cell receptor stimulation involves intracellular signaling events that ultimately lead to the activation of transcription factors, such as NF‐κB. We explored the involvement of the NF‐κB components IKK‐2 and NEMO in NTN, by using cell‐specific knockouts of IKK‐2 and NEMO in CD4+ T lymphocytes. Our results demonstrate that although the course of disease was not grossly altered in CD4xIKK2Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…NEMO mutation causes immune deficiency, which impairs lymph node formation in hemizygous mice and men [ 52 ]. In addition, NEMO knockout in T-lymphocyte induces the expression of Th17-related cytokines in spleen CD4+ T cells, and interrupted the canonical NF-κB pathway in an experimental nephrotoxic nephritis mouse model [ 53 ]. Our data revealed that IKKγ mRNA and protein levels gradually upregulated from day 13 to 25 of pregnancy in the maternal spleen, and IKKγ protein was located in the capsule, trabeculae and splenic cords.…”
Section: Discussionmentioning
confidence: 99%
“…NEMO mutation causes immune deficiency, which impairs lymph node formation in hemizygous mice and men [ 52 ]. In addition, NEMO knockout in T-lymphocyte induces the expression of Th17-related cytokines in spleen CD4+ T cells, and interrupted the canonical NF-κB pathway in an experimental nephrotoxic nephritis mouse model [ 53 ]. Our data revealed that IKKγ mRNA and protein levels gradually upregulated from day 13 to 25 of pregnancy in the maternal spleen, and IKKγ protein was located in the capsule, trabeculae and splenic cords.…”
Section: Discussionmentioning
confidence: 99%
“…These data therefore provide further insight into how constitutive activation of the canonical and alternative NFκB pathways might drive pathology in chronic inflammation and autoimmune disease and demonstrate that the adequate balance of NFκB activity, regulated by NFκB2 p100, is essential for maintaining optimal Treg function and immune tolerance (115). We have recently shown in two experimental models of renal injury that the non-canonical NFκB signaling pathway is critical for Th17 cell induction and that the Th17 cell immune function depends on the fine-tuning of canonical NFκB signaling (92, 141). The crosstalk between canonical and non-canonical NFκB signaling in the complex regulation of Th17 cells and Tregs warrants further investigation to identify potent candidate genes for the manipulation of pathogenicity of Th17 cells without affecting nonpathogenic Th17 and Treg cells that may be critical for tissue homeostasis in renal diseases (109, 142, 143) (Figure 2).…”
Section: Renal Disease—nfκb Pathway Crosstalkmentioning
confidence: 99%